Rationale and population-based prospective cohort protocol for the disadvantaged populations at risk of decline in eGFR (CO-DEGREE) - Antonio Bernabe-Ortiz; Neil Pearce; Hans Kromhout; Pablo Perel; Liam Smeeth; Cristina O’Callaghan-Gordo; Jason Glaser; Kristina Jakobsson; Dorothea Nitsch; Ben Caplin; Nalika Gunawardena; Adeera Levin; et al. (BMJ Open)
Introduction A recently recognised form of chronic kidney disease (CKD) of unknown origin (CKDu) is afflicting communities, mostly in rural areas in several regions of the world. Prevalence studies are being conducted in a number of countries, using a standardised protocol, to estimate the distribution of estimated glomerular filtration rate (eGFR), and thus identify communities with a high prevalence of reduced glomerular filtration rate (GFR). In this paper, we propose a standardised minimum protocol for cohort studies in high-risk communities aimed at investigating the incidence of, and risk factors for, early kidney dysfunction.Methods and analysis This generic cohort protocol provides the information to establish a prospective population-based cohort study in low-income settings with a high prevalence of CKDu. This involves a baseline survey that included key elements from the DEGREE survey (eg, using the previously published DEGREE methodology) of a population-representative sample, and subsequent follow-up visits in young adults (without a pre-existing diagnosis of CKD (eGFR<60 mL/min/1.73m2), proteinuria or risk factors for CKD at baseline) over several years. Each visit involves a core questionnaire, and collection and storage of biological samples. Local capacity to measure serum creatinine will be required so that immediate feedback on kidney function can be provided to participants. After completion of follow-up, repeat measures of creatinine should be conducted in a central laboratory, using reference standards traceable to isotope dilution mass spectrometry (IDMS) quality control material to quantify the main outcome of eGFR decline over time, alongside a description of the early evolution of disease and risk factors for eGFR decline.Ethics and dissemination Ethical approval will be obtained by local researchers, and participants will provide informed consent before the study commences. Participants will typically receive feedback and advice on their laboratory results, and referral to a local health system where appropriate.